Sports Biomechanics Laboratory Davis University California
The Sports Biomechanics Laboratory is concerned with the enhancement of understanding and performance in athletic events through modeling, simulation and measurement. The laboratory is engaged in the study of the mechanics of various sports activities, including both the motion of athletes and the motion of sports implements and vehicles. The emphasis is on developing mathematical and computational models for events which allow increased understanding, performance evaluation and optimization, as well as intelligent implement and vehicle design. Often the goal is the development of methods and systems for providing real time feedback of athlete performance during training. Computational facilities include IBM RISC 6000 high speed graphics workstations as well as Macintosh and IBM PC's. Computational approaches feature heavy use of graphical animation, often in real time, for the interpretation of model outputs. Experimental facilities include an ExpertVision 200 Hz kinematic motion analysis system for measurement and analysis of both athlete and implement motion. Graduate and undergraduate students come mainly from the Mechanical Engineering Department and the Biomedical Engineering Graduate Group. The laboratory's activities are made possible by a large number of financial and in-kind sponsors .